Evaluating the Effectiveness of Construction Management on Quality, Time, Cost, and Risk Performance in the Nuclear Medicine Building Project at Dr. Soedarso Regional General Hospital, Pontianak - Iin Arianti; Sarah Safira; Salwa Putri Nabilla; Muhammad Rafani; Nurul Fitriani; Wattini Wattini; Agus Eko Tejo Sasongko (LPPM Institut Pendidikan Nusantara Global, 2025)
The Nuclear Medicine Building is a strategic healthcare facility that utilizes open radiation sources for diagnosis and treatment. Due to its high structural complexity and radiological risks, this study aims to analyze the construction management implementation of the Nuclear Medicine Building project at Dr. Soedarso Regional General Hospital, Pontianak. The research utilizes primary data from field observations and secondary data from project documents, analyzed through four critical aspects: cost, time, quality, and human resources. The study produces an Implementation Budget Plan (RAP) totaling IDR 7,904,689,106.53. Time management planning establishes a project duration of 15 weeks or 108 calendar days, utilizing Network Planning and Bar Charts to monitor the critical path. Quality management is implemented through a quality control table to ensure technical specification compliance, while human resource planning identifies a peak labor requirement of 100 workers per day during the 7th week. Analytically, the integration of cost and time in this project validates the